MODAL SOSIAL DALAM KEGIATAN PENYULUHAN PERTANIAN DI KOTA KENDARI - Niya, Wa Ode Nur; Taufik, Yani; Salahuddin, Salahuddin; Malik, Nurhayu (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The purpose of this investigation is to (1) determine the identity of agricultural advisor in Kendari City; and (2) knowing the social capital of extension workers in carrying out extension activities in the Kendari City. The samples in the study were all agricultural extension workers in Kendari City. The data analysis used in this study Is a descriptive quantitative analysis that is processed using the class interval formula. The results of this study showed that the social capital of Kendari City is generally  in the good category. This can also be seen from the aspects of trust, reciprocity and social interaction are in the good category. This means that agricultural extension workers in Kendari City have implemented the elements of social capital well.